Former privileged transit railway lines as instruments of cross-border integration? A comparative study of the lines in the Czech-Polish borderland - Boháč, Artur; Drápela, Emil; Czepil, Bartosz (European Spatial Research and Policy, 2026)
Privileged transit traffic or similar railway lines illustrate Central Europe’s historical interdependence and the persistence of infrastructural anomalies. This paper analyses their contemporary role as instruments of cross-border integration through two Czech-Polish cases: the Liberec–Bogatynia–Zittau–Varnsdorf–Seifhennersdorf line in the west, which also includes German territory, and the Jeseník–Głuchołazy–Krnov line in the east. Using a qualitative comparative approach that integrates document analysis, field observation, and stakeholder interviews, the study assesses how governance density, fare regimes, and accessibility influence the dimensions of cross-border integration. The results reveal contrasting trajectories. The Zittau line, embedded in trilateral governance frameworks and supported by fare integration, enables frequent services and symbolises everyday transnational normality, except for a small section. Conversely, the Głuchołazy line remains hindered by outdated legal arrangements, low frequency, and peripheral infrastructure. These differences underscore that multilevel governance and fare harmonisation are crucial preconditions for cohesion, while regulatory fragmentation and institutional inertia exacerbate marginality. Overall, the study argues that privileged transit railway connections, if supported by regional advocacy and coordinated investment, can evolve from historical exceptions into agents of European integration.